Hospital Use, Morbidity, and Cancer Risk by Age Group in Neurofibromatosis Type 1: A Nationwide Retrospective Cohort Study - Minsu Kim; Suhyun Han; Chong Won Choi; Bo Ri Kim; Sang Woong Youn (Acta Dermato-Venereologica)
Neurofibromatosis type 1 (NF1) affects multiple organs progressively, leading to a shortened life expectancy. This study aimed to identify the complications that are prominent in each age group by comparing 28,082 patients with NF1 and 84,246 matched controls. Benign and malignant neoplasms along with neurological complications were the primary contributors to hospital use across most age groups. Respiratory and circulatory disorders were a common cause of hospital use in children and older adults, respectively. Except for soft tissue and central nervous system-originated malignancies, which are well-established NF1-related tumours, the highest rate ratios (RR) of malignancies with statistical significance was observed in the adrenal gland (0–9 years, RR 50.67, 95% CI 6.74–380.76); female genital organs (10–14 years, RR 12.06, 95% CI 1.35–107.93); respiratory and intrathoracic organs (15–19 years, RR 15.10, 95% CI 1.76–129.22; 20–29 years, RR 7.59, 95% CI 2.94–19.56; ≥ 60 years, RR 1.38, 95% CI 1.18–1.61); lip, oral cavity, and pharynx (30–39 years, RR 6.11, 95% CI 1.53–24.42); and bone and articular cartilage (40–49 years, RR 3.06, 95% CI 1.37–6.81; 50–59 years, RR 4.73, 95% CI 2.35–9.50). Comorbidities and malignancies that predominantly affect patients vary by age group; physicians should be aware of the appropriate management strategies throughout their lifespan.